Analyse De Limpact Du Microcredit Sur Lemploi Des Jeunes Ruraux Dans La Region De Lextreme Nord Cameroun : Cas Du Programme Dappui Au Developpement Des Emplois Ruraux (PADER) (Global Journal of Human-Social Science, 2021)
The Cameroonian State, in order to fight against unemployment of its population, has developed and put into practice a whole set of public policy instruments. The National Employment Fund (FNE) is an instrument of choice in this policy. After 30 years of existence, this structure must be evaluated to determine whether it is achieving the objectives that have been assigned to it. To this end, by working with beneficiaries financed by the FNE through the PADER program in the Far North region during 2012, we determined the impact of microcredits granted to populations by this structure to fight against unemployment in rural areas. Using a logistic regression model, we were able to capture the induced effects of this program in our study population. According to the results obtained, the amount of the microcredit is significant in the fight against unemployment, but is low to be able to hire other people, moreover the only sector for which the amount provided has real impact is that of the agricultural sector, the other activities requiring additional contributions.
Keywords: FNE: pader; binary logistic regression; diamaré; impact study rural self-employment; microcredit